2014
DOI: 10.1111/cts.12133
|View full text |Cite
|
Sign up to set email alerts
|

People United to Sustain Health (PUSH): A Community‐Based Participatory Research Study

Abstract: The prevention of weight gain to address the obesity epidemic rather than weight loss involves promoting small changes in food choices and physical activity. People United to Sustain Health (PUSH) was designed to increase fruit and vegetable consumption, physical activity, and food security to prevent weight gain in rural adults. Forty-nine participants were randomized into a treatment group which received access to a “Rolling Store,” nutrition education and physical activity, and a control group which receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Compared to the present study, interventions on reducing fat and sugar intake demonstrated higher effect on weight reduction [13,51]. Consistent with our findings, most of the interventions could not produce reduction in SBP [44,51]; however, a few interventions reported an increase in both SBP and DBP [52]. Diastolic blood pressure reduced significantly in the present study which is an indicator of salt sensitivity [53] and has been shown to be related to urinary sodium excretion in hypertensive populations [54].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Compared to the present study, interventions on reducing fat and sugar intake demonstrated higher effect on weight reduction [13,51]. Consistent with our findings, most of the interventions could not produce reduction in SBP [44,51]; however, a few interventions reported an increase in both SBP and DBP [52]. Diastolic blood pressure reduced significantly in the present study which is an indicator of salt sensitivity [53] and has been shown to be related to urinary sodium excretion in hypertensive populations [54].…”
Section: Discussionsupporting
confidence: 86%
“…The possible explanation could be low self-efficacy in changing the taste developed over the years for food high in salt which was a major concern raised by participants during formative research. The intervention had a similar effect on increasing fruit and vegetable intake as reported from developed countries using traditional methods of education [44,47] and mobile technology [48]. In contrast, a lifestyle intervention in Sweden using counseling, group discussions on healthy eating by health workers and cooking classes by a chef to increase fruit and vegetable intake and to reduce fat intake, could not produce a significant change in behaviour outcomes [49].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Most previous studies have targeted individuals at high risk of disease as ‘at risk’ individuals are more motivated than the general population; other studies have had a small sample size or non-representative sample [4043]. Instead of overall health promotion, most of the studies to date have focused on single outcome such as reducing weight, blood pressure or cancer prevention [40,44,45]. Some trials have provided incentives to the participants in the form of provision of diets free of cost, while others made fruits and vegetables available at low cost in the study area [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of overall health promotion, most of the studies to date have focused on single outcome such as reducing weight, blood pressure or cancer prevention [40,44,45]. Some trials have provided incentives to the participants in the form of provision of diets free of cost, while others made fruits and vegetables available at low cost in the study area [44,45]. In some trials, the control group did not receive any intervention which raises questions about study validity [41,46,47].…”
Section: Discussionmentioning
confidence: 99%